Analysis of channel allocation scheme for wireless cellular networks. (9th April 2009) - Du, Wenfeng; Jia, Weijia; Wang, Guojun; Lu, Wenyan
Compared to wired networks, the communication bandwidth in the wireless networks is limited. In trying to achieve QoS guaranteed wireless services, efficient utilisation of bandwidth resources becomes a fundamental issue. A number of channel allocation schemes have been proposed to fully utilise the wireless bandwidth, but many of them just proposed the channel allocation scheme without presenting a specific channel allocation model. In this paper, we propose and analyse three different channel allocation schemes for wireless networks. We build three system models based on a two-dimensional Markov chain to compute the performance of base station in terms of the new call blocking probability, the handover dropping probability, and the channel utilisation.